2009
DOI: 10.1056/nejmoa0810266
|View full text |Cite|
|
Sign up to set email alerts
|

Adjuvant Chemotherapy in Older Women with Early-Stage Breast Cancer

Abstract: BACKGROUND Older women with breast cancer are underrepresented in clinical trials, and data on the effects of adjuvant chemotherapy in such patients are scant. We tested for the noninferiority of capecitabine as compared with standard chemotherapy in women with breast cancer who were 65 years of age or older. METHODS We randomly assigned patients with stage I, II, IIIA, or IIIB breast cancer to standard chemotherapy (either cyclophosphamide, methotrexate, and fluorouracil or cyclophosphamide plus doxorubicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
332
3
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 505 publications
(357 citation statements)
references
References 38 publications
6
332
3
16
Order By: Relevance
“…Results indicated that the efficacy of UFT as an adjuvant treatment was comparable with that of CMF. On the other hand, Cancer and Leukemia Group B (CALGB) reported that a 4.5-month administration of capecitabine was inferior to CMF/AC (doxorubicin (ADM) þ CPA) in elderly breast cancer patients (Muss et al, 2009). This disagreement among results, including those of this study, might be partly explained by the difference in the duration of treatment with oral fluoropyrimidines.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that the efficacy of UFT as an adjuvant treatment was comparable with that of CMF. On the other hand, Cancer and Leukemia Group B (CALGB) reported that a 4.5-month administration of capecitabine was inferior to CMF/AC (doxorubicin (ADM) þ CPA) in elderly breast cancer patients (Muss et al, 2009). This disagreement among results, including those of this study, might be partly explained by the difference in the duration of treatment with oral fluoropyrimidines.…”
Section: Resultsmentioning
confidence: 99%
“…Others studies on adherence to capecitabine were published, and the data were similar to what was observed in the present study, especially in relation to breast cancer. Only 76% of the elderly patients with breast cancer received 80% or more of the prescribed doses (19) . On the other hand, in a younger breast cancer population, the mean adherence found was greater than 96% (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Because women aged Ͼ80 years make up almost 15% of the breast cancer population, it is worrisome that these women apparently do not profit from the advances made. A number of authors have argued that older breast cancer patients may not get appropriate treatment [5][6][7]9]. In a Swiss population-based study of breast cancer patients diagnosed in 1989 -1999, it was shown that the treatment of older women differed from that of the younger age groups.…”
Section: Discussionmentioning
confidence: 99%
“…For younger patients, a strong increase in adjuvant chemotherapy was seen, but very few elderly patients received adjuvant chemotherapy. However, recent trials suggest that, in fit elderly patients, standard chemotherapy is both effective and tolerated [5].…”
Section: Undertreatmentmentioning
confidence: 99%